Teacher Competence Based on National Education Standards as a Pillar of Quality Learning: A Theoretical Analysis for Elementary Schools in Indonesia - Fannisa, Hani; Zain, Bella Putri; Hafidza, Hikmah; Mardin, Aznil; Wahyuni, Molli (Universitas Pahlawan Tuanku Tambusai, 2025)
Primary education is a crucial phase in shaping students’ intelligence, character, and morality. Its quality is largely determined by the role of professional and competent teachers. This article aims to theoretically analyze the role of teacher competence based on the National Education Standards (SNP) as a pillar of quality learning in elementary schools. Although numerous studies discuss teacher competence and its impact on learning quality, research that specifically positions the SNP as the primary analytical framework for evaluating teacher competence in elementary schools remains very limited. This study employs a literature review approach with a theoretical-qualitative analysis method, drawing on legal sources, national literature, and international research findings from 2015 to 2025. The findings show that the four teacher competencies in the SNP (pedagogical, personal, social, and professional) play a strategic role in creating effective, humanistic, and innovative learning. Pedagogical competence supports student-centered learning, personal competence shapes exemplary behavior, social competence fosters inclusive interaction, and professional competence enhances subject mastery and teaching creativity. International studies reinforce that the integration of these four competencies positively impacts students’ learning motivation and achievement. This study emphasizes the importance of strengthening continuous teacher training and implementing evidence-based policies to develop professional teachers with global competitiveness.